Respostas

2014-02-03T21:10:17-02:00
Δ = b² -4ac
Δ = (-7)² -4 *3 * 2
Δ = 49 -24
Δ = 25
x' = (-b + √∆)/ 2a
(-(-7) + 5)/2 * 3
(7 + 5)/6
12/6
2
x'' = (-b - √∆)/ 2a
(-(-7) - 5)/2 * 3
(7 - 5)/6
2/6


S={2,2/6}
2014-02-03T21:26:52-02:00
3x²-7x+2=0                       ×= -b ≥ √Δ                 ×¹= 7+5 =  12 =  2
Δ=b² -4.a.c                              2.a                             6        6
Δ=(-7)² -4.3.2                               
Δ= 49 - 24                        ×= 7 ≥ √25                ×²= 7-5 =  =  
Δ=25                                       2.3                           6       6     3

R.: x¹= 2 e x²=1
                    3